ANALYSIS OF SOCIO-ECONOMIC CONDITIONS, COMMUNITY UNDERSTANDING, SERVICE QUALITY ON THE PROBABILITY OF BRIBERY THROUGH LICENSING TRANSPARENCY AS INTERVENING VARIABLES - Daniel Ebenezer Silaban; Raina Linda Sari; Irsad Lubis (UNIVERSITAS PAKUAN, 2022)
This research is motivated by bribery cases that have occurred both in North Sumatra. This indicates that there are problems that occur in the Investment Office so that officers have great potential to be bribed by the public. On that basis, the researchers tried to analyze socio-economic conditions, public understanding and service quality at the One Stop Integrated Licensing and Investment Service Office of North Sumatra Province on the probability of bribery with licensing transparency seen as an indirect or intervening variable. The type of research that will be conducted is quantitative research. Quantitative methods are used to see the similarities in responses to perceptions of the probability of bribing that occur in the One Stop Integrated Licensing and Investment Service Office of North Sumatra Province. This research is also specifically an Explanatory Survey, namely research that explains the relationship between the variables studied. The results of this study show that of the eight effects there are four hypotheses that have a significant effect, namely, public understanding of licensing transparency, public understanding of the probability of bribery, service quality towards licensing transparency and licensing transparency on the probability of bribery. In addition, there are three hypotheses that have no effect, namely socio-economic on the transparency of licensing, socio-economic on the probability of bribery and service quality on the probability of bribery. Furthermore, on the indirect effect, it can be seen that socioeconomics does not affect the probability of bribery through licensing transparency as an intermediate/indirect variable, public understanding affects the probability of bribery through licensing transparency as an intermediate/indirect variable and service quality affects the probability of bribery through licensing transparency as intermediate/indirect variable.